Induction of bacteremia in newborn rats by Escherichia coli K1 is correlated with only certain O (lipopolysaccharide) antigen types. - Pluschke, G (1983)
A total of 95 Escherichia coli strains (O1:K1, O7:K1, or O18:K1), obtained from different sources of human infections and from healthy individuals, were analyzed for the ability to cause bacteremia after colonizing the gut of newborn rats. Strains of all three serotypes were able to multiply extensively in the gut after oral inoculation and to translocate (in small numbers) to the mesenteric lymph nodes. With only few exceptions, O7:K1 and O18:K1 strains were able to cause bacteremia, while O1:K1 strains could not. Mixed-infection experiments revealed that the bacteria present in the blood during a case of bacteremia are in most cases the descendants of one cell that has multiplied extraintestinally after translocation to the mesenteric lymph nodes. It appears that virulent O7:K1 and O18:K1, but not avirulent O1:K1, bacteria are able to multiply directly in the bloodstream of the newborn rats. No correlation between virulence and the source of isolation of the different strains was observed. Disease isolates thus do not seem to differ from fecal isolates of the same serotype in special virulence properties. The differences in virulence among different O serotypes of K1 E. coli observed in the rat model were comparable to their relative frequency of isolation from meningitis in newborn children.